Different Responses of Soil Environmental Factors, Soil Bacterial Community, and Root Performance to Reductive Soil Disinfestation and Soil Fumigant Chloropicrin - Zhan, Yu; Yan, Ning; Miao, Xinyue; Li, Qiong; Chen, Changbao (Frontiers in Microbiology, 2021)
Reductive soil disinfestation (RSD) and soil fumigant chloropicrin (SFC) are two common agricultural strategies for the elimination of soil-borne pathogens. However, the differences in soil environmental factors, soil bacterial microbiome and root performance between SFC and RSD are poorly understood. In this study, three soil treatments, un-treated control (CK), SFC with 0.5 t ha−1 chloropicrin, RSD with 15 t ha−1 animal feces, were compared. We evaluated their effects on soil environmental factors, bacterial community structure, and root activity using chemical analysis and high-throughput sequencing. RSD treatment improved soil composition structure, bacterial diversity, and root performance to a greater extent. Carbon source utilization preference and bacterial community structure were strikingly altered by SFC and RSD practices. Bacterial richness, diversity, and evenness was notably lowered in the SFC and RSD treated soil compared with the CK treated soil. However, RSD treated soil harbored distinct unique and core microbiomes that were comprised of more abundant and diverse potentially disease-suppressive and organic-decomposable agents. Also, soil bacteria diversity and composition were closely related to soil physicochemical properties and enzyme activity, of which pH, ANa, AMg, AMn, TNa, TCa, TCu, TSr, S-UE, S-ACP and S-SC were the main drivers. Moreover, RSD treatment also significantly increased ginseng root activity. Collectively, these results suggest that RSD practices could considerably restore soil nutrient structure and bacterial diversity, and improve root performance, which can be acted as a potential agricultural practice for the development of disease-suppressive soil.